Analisis Hukum dan Perlindungan Anak Terkait Hak Asasi Manusia dalam Kasus Tindak Pidana Pencabulan Anak di Bengkulu Utara - Chichi Savitri (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This study discusses "Case studies regarding criminal acts of sexual abuse against children in the North Bengkulu region, in 2023". This research was motivated by a number of confusing cases. Therefore, it is necessary to understand what drives sexual criminal behavior and how law enforcement attempts to address or minimize cases that reveal children. This type of research is normative juridical. The data source is secondary data. This data was taken from a report to the police on April 15 2023 regarding child molestation and same-sex molestation precisely in the jurisdiction of the North Bengkulu Police. From the research results, the cause of sexual abuse in North Bengkulu district, namely the cause of criminal acts of sexual abuse against minors in the jurisdiction of the North Bengkulu Police, is an internal factor (moral factor). Cancel. factors, education, sex, bad habits, etc.). External factors (economic factors, free social environment, opportunities). The crime of obscenity against minors in the jurisdiction of the North Bengkulu Police is caused by giving the perpetrator the opportunity to realize his own evil intentions, and does not allow him to control the consequences, especially the bad consequences of the perpetrator's own sexuality. help. The perpetrator's habit of wanting small children to satisfy his own desires. The way to overcome or minimize sexual violence in North Bengkulu is to take repressive action against perpetrators of violence against children, especially in accordance with applicable laws and regulations.